Effect of Cd-annealing on the IR transmittance of CdTe wafers grown by the Bridgman method - Kim, W.J.; Park, M.J.; Kim, S.U.; Lee, T.S.; Kim, J.M.; Song, W.J.; Suh, S.H. (1990)
CdTe crystals were grown by the vertical Bridgman method. CdTe wafers processed from the crystals showed p-type conductivity and low IR transmittance. Isothermal annealing in Cd atmosphere for 5 h at 600° C enhanced the IR transmittance of the wafer up to 65%. The annealed wafer showed n-type conductivity with a carrier concentration of 2.1 × 1015 cm-3. The high IR transmittance obtained is attributed to annihilation of Cd vacancies during annealing in Cd atmosphere. The IR transmittance of CdTe wafers increased with increasing annealing time from 0.5 to 5 h. Annealed thickness could be calculated from the IR transmittance by assuming an abrupt junction between the annealed surface and unannealed core. The annealed thickness followed the usual time dependence of t1 2. ？ 1990.
Keywords: Crystals--Growing; Heat Treatment--Annealing; Infrared Radiation--Transmission; Bridgman Method; Cadmium Telluride; Semiconducting Cadmium Compounds